Inhibition of rat locus coeruleus neurons by prostaglandin E2 EP3 receptors: pharmacological characterization ex vivo - Nazabal, Amaia; Mendiguren, Aitziber; Pineda, Joseba (Frontiers in Pharmacology, 2023)
Prostaglandin E2 (PGE2) is an inflammatory mediator synthesized by the brain constitutive cyclooxygenase (COX) enzyme. PGE2 binds to G protein-coupled EP1-4 receptors (EP1 to Gq, EP2,4 to Gs, and EP3 to Gi/o). EP2, EP3 and EP4 receptors are expressed in the locus coeruleus (LC), the main noradrenergic nucleus in the brain. EP3 receptors have been explored in the CNS, although its role regulating the LC neuron activity has not been pharmacologically defined. Our aim was to characterize the function of EP3 receptors in neurons of the LC. Thus, we studied the effect of EP3 receptor agonists on the firing activity of LC cells in rat brain slices by single-unit extracellular electrophysiological techniques. The EP3 receptor agonist sulprostone (0.15 nM -1.28 µM), PGE2 (0.31 nM -10.2 µM) and the PGE1 analogue misoprostol (0.31 nM -2.56 µM) inhibited the firing rate of LC neurons in a concentration-dependent manner (EC50=15 nM, 51 nM, and 110 nM, respectively). The EP3 receptor antagonist L-798,106 (3-10 µM), but not the EP2 (PF-04418948, 3-10 µM) or EP4 (L-161,982, 3-10 µM) receptor antagonists, caused rightward shifts in the concentration-effect curves for the EP3 receptor agonists. Sulprostone-induced effect was attenuated by the Gi/o protein blocker pertussis toxin (PTX, 500 ng ml -1 ) and the inhibitors of inwardly rectifying potassium channels (GIRK) BaCl2 (300 µM) and SCH-23390 (15 µM). LC neuron firing activity is regulated by EP3 receptors, presumably by an inhibitory Gi/o protein-and GIRK-mediated mechanism.